Conceptual Design of Smart Network Adaptive Traffic Light in Creating Low-Carbon City - Misnan, Mohamad Farid; M. Thamrin, Norashikin; Megat Amin, Megat Syahirul; Abu Bakar, Zahari (International Journal of Integrated Engineering, 2023)
The research led to the development of a smart sensory network adaptive traffic light to optimise traffic flow and reduce congestion on Jalan Persisiran Seri Alam in Pasir Gudang. This system, with variable time management, can reduce the time spent at traffic junctions and the carbon emitted by vehicles, thus supporting the SDG 11 for low carbon smart city. By integrating the dynamic duration of each traffic signal on each dense pathway, this system can help reduce traffic congestion, fuel consumption, and CO2 emissions. It can also ensure that traffic is managed in a more efficient manner, thus improving the quality of life for the people of Pasir Gudang. The success of this system will be a major step towards achieving the goal of a low carbon smart city, as it will help to reduce air pollution, noise pollution and improve road safety. Additionally, it can help to improve the efficiency of traffic flow, leading to better traffic management and reduced congestion.